Functional Characterisation of the Autophagy ATG12 5/16 Complex in Dictyostelium discoideum - Karow, Malte; Fischer, Sarah; Meßling, Susanne; Konertz, Roman; Riehl, Jana; Xiong, Qiuhong; Rijal, Ramesh; Wagle, Prerana; Clemen, Christoph S.; Eichinger, Ludwig (Cells, 2020)
Macroautophagy, a highly conserved and complex intracellular degradative pathway, involves more than 20 core autophagy (ATG) proteins, among them the hexameric ATG12 5/16 complex, which is part of the essential ubiquitin-like conjugation systems in autophagy. Dictyostelium discoideumatg5 single, atg5/12 double, and atg5/12/16 triple gene knock-out mutant strains displayed similar defects in the conjugation of ATG8 to phosphatidylethanolamine, development, and cell viability upon nitrogen starvation. This implies that ATG5, 12 and 16 act as a functional unit in canonical autophagy. Macropinocytosis of TRITC dextran and phagocytosis of yeast were significantly decreased in ATG5¯ and ATG5¯/12¯ and even further in ATG5¯/12¯/16¯ cells. In contrast, plaque growth on Klebsiella aerogenes was about twice as fast for ATG5¯ and ATG5¯/12¯/16¯ cells in comparison to AX2, but strongly decreased for ATG5¯/12¯ cells. Along this line, phagocytic uptake of Escherichia coli was significantly reduced in ATG5¯/12¯ cells, while no difference in uptake, but a strong increase in membrane association of E. coli, was seen for ATG5¯ and ATG5¯/12¯/16¯ cells. Proteasomal activity was also disturbed in a complex fashion, consistent with an inhibitory activity of ATG16 in the absence of ATG5 and/or ATG12. Our results confirm the essential function of the ATG12 5/16 complex in canonical autophagy, and furthermore are consistent with autophagy-independent functions of the complex and its individual components. They also strongly support the placement of autophagy upstream of the ubiquitin-proteasome system (UPS), as a fully functional UPS depends on autophagy.
CRIS-Team Scopus Importer:2020-05-22
Keywords: ATG12 5/16 complex; autophagy; Dictyostelium; phagocytosis; pinocytosis; proteasome; ubiquitin-like protein; UPS